Influence of ADAM10 Polymorphisms on Plasma Level of Soluble Receptor for Advanced Glycation End Products and The Association With Alzheimer’s Disease Risk - Huang, Wen-Hui; Chen, Wei; Jiang, Lian-ying; Yang, Yi-Xia; Yao, Li-Fen; Li, Ke-Shen (Frontiers in Genetics, 2018)
To determine the role of A disintegrin and metalloproteinase 10(ADAM10) in genetic susceptibility to Alzheimer's disease in a representative Chinese sample, we genotyped 362 Alzheimer's disease (AD) patients and 370 healthy controls for rs514049A/C and rs653765C/T polymorphisms of the ADAM10 promoter using the SNaPshot technique. We also examined the potential impact of this polymorphism on plasma level of soluble receptor for advanced glycation end products (sRAGE), a decoy receptor whose reduction has been associated with a higher risk of AD. Our results suggested no significant differences in the distributions of genotype or allele between AD patients and control subjects. However, age at onset stratification analysis revealed that there were significant differences in the genotype (P=0.015) and allele (P=0.020) of the rs5653765 SNP. Furthermore, the rs5653765 CC genotype in late onset AD(LOAD) showed a lower ADAM10 level compared to healthy controls, and the rs653765 CC polymorphism had the ability to regulate the production of the ADAM10 substrates sRAGE. In contrast, the polymorphism of rs514049 was not statistically associated with AD. The present study indicated rs653765 polymorphism of ADAM10 might be associated with the risk and the development of LOAD. In particular, the risk CC genotype may decrease the expression of ADAM10 and then influence the plasma levels of sRAGE, thus possibly in correlation with affecting clinical progression of AD.